Oligarchy and Merchant Capitalism in lower Andalusia under the Catholic Kings: the case of Córdoba and Jerez de la Frontera. - Edwards, J.H. (Historia. Instituciones. Documentos, 2018)
RESUMEN: ABSTRACT: